Identification of Knee Effusions With Ultrasound: A Comparison of Three Methods. Issue 1 (6th January 2022) - Cushman, Daniel M.; Ross, Brendon; Teramoto, Masaru; English, Joy; Joyner, James R.; Bosley, Justin
Abstract : Objectives: To determine whether simple methods can improve identification of suprapatellar joint fluid during sonographic evaluation of the knee. Design: Prospective cohort study. Setting: Outpatient orthopaedic clinic. Patients: Fifty-two patients were sequentially recruited from an orthopaedic clinic. Interventions: Bilateral sonographic evaluation of the suprapatellar recess with static scanning, parapatellar pressure, or patient-initiated quadriceps contraction. Main Outcome Measures: Identification of fluid in the suprapatellar recess. Results: Fifty-two patients (104 knees), consisting of 57 (54.8%) painful knees, were examined. Static scanning identified 45 effusions, parapatellar pressure identified 58 effusions, and quadriceps contraction identified 77 effusions. Quadriceps contraction was superior to parapatellar pressure for identifying an effusion { P < 0.001, proportion ratio [PR] = 1.33 [95% confidence interval (CI) = 1.16, 1.52]}, painful knee effusions [ P = 0.036, PR = 1.24 (95% CI = 1.06-1.44)], and painless knee effusions ( P = 0.006, PR = 1.50 [95% CI = 1.16-1.93]). Both methods were superior to static scanning. Parapatellar pressure identified effusions in 16.9% of knees not seen on static scanning, whereas quadriceps contraction identified effusions in 54.2% of knees not seen on static scanning. Inter-rater reliability kappa values were 0.771 for static scanning (95% CI = 0.605-0.937), 0.686 for parapatellar pressure (95% CI = 0.531-0.840), and 0.846 for quadriceps contraction (95% CI = 0.703-0.990). Conclusions: Parapatellar pressure and patient-initiated quadriceps contraction both improve sonographic detection of suprapatellar joint fluid with high inter-rater reliability; however, quadriceps contraction was superior to parapatellar pressure when assessing for grade 1 or occult effusions.